INSTITUTIONAL CONSULTING IN THE U.S. HIGHER EDUCATION: SUPPORTING EMERGING LEADERS AND ADMINISTRATIVE TEAMS (Comparative Professional Pedagogy, 2025)
The importance of institutional consulting is substantiated as an effective strategic management tool aimed at developing human capital, strengthening leadership competencies, and supporting emerging leaders and administrative teams in the USA. The article explores the phenomenon of leadership as a key factor in ensuring the quality, innovation, and competitiveness of higher education institutions amid ongoing educational transformation. University-based consulting in leadership development encompasses psychological and pedagogical support (such as shaping an individual leadership style), coaching and facilitation of team projects, expert guidance in designing and implementing leadership initiatives, and the creation of internal leadership centers for the development of leadership potential among students, faculty, and administrators. The study analyzes leadership development programs at leading U.S. universities, which combine theoretical training, mentorship, coaching, facilitation, and feedback to support individualized management skill development within dynamic academic environments. The content of these programs is oriented toward enhancing strategic thinking, agile leadership, organizational culture formation, and increasing leadership effectiveness. A comprehensive approach to leadership development in the U.S. academic environment is based on the integration of educational and managerial strategies, a focus on personalized learning experiences, interdisciplinarity, and adaptability to change. The study emphasizes the relevance of adapting effective U.S. models of institutional consulting to the needs of Ukrainian higher education institutions in order to build a modern leadership corps capable of responding effectively to the challenges of educational reform and global transformations. Implementing this experience in domestic universities could be an effective means of forming a talent pool for the education management system, developing university autonomy, and improving the overall quality of the educational process.
Keywords: institutional consulting; higher education; universities; leadership potential; human resources; the USA; university management; programs; leadership competence; mentoring; coaching